Employment Development Based on the Qur'an: Thematic Analysis of Employment Verses - Shafaadhila Nur Azizah; Abdul Matin Bin Salman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses complex and interrelated problems in employment development. One of the factors influencing this problem is the lack of human resource capacity caused by an education and training system that is not in line with market needs. To overcome this problem, efforts are needed to improve the quality of education and training, create jobs in line with the growth of the workforce, and protect labor rights. This article links the Al-Qur'an perspective in looking at employment which is presented with qualitative data processing methods and the use of Maudhu'i Hayy Al Farmawi's analytical techniques by combining several verses that suit the theme. It is hoped that this article can provide insight into issues regarding employment opportunities, work quality, and protection of labor rights contained in the Qur'an.